A Fast Shift-Splitting Method for Singular Generalized Saddle Point Problems (Journal of Mathematical Study, 2021)
For the iteration solution of singular generalized saddle point problems, afast shift-splitting iteration method based on shift-splitting technique and symmetricand skew-symmetric splitting with respect to the upper-left block of the system matrixis proposed in this paper. Semi-convergence of the proposed method is carefullystudied for singular case, and the conditions guaranteeing the semi-convergence arederived. Numerical experiments of a class of linearized Navier-Stokes equations areimplemented to demonstrate the feasibility and effectiveness of the proposed method.
Keywords: Shift-splitting iteration method; singular generalized saddle point problems; semi-convergence.